Resistance risk and molecular mechanism associated with resistance to picoxystrobin in Colletotrichum truncatum and Colletotrichum gloeosporioides - Niu-niu SHI; Jin-pan LIAN; De-zhu QIU; Fu-ru CHEN; Yi-xin DU (Journal of Integrative Agriculture, 2023)
Anthracnose, caused by Colletotrichum truncatum and C. gloeosporioides, is amongst the most serious diseases of soybean in China. Picoxystrobin, a quinone outside inhibitor fungicide, is commonly used for the control of anthracnose. Its resistance risk and mechanism in C. truncatum and C. gloeosporioides are unclear. In this study, the sensitivities of 128 C. truncatum and 121 C. gloeosporioides isolates to picoxystrobin were investigated, and unimodal distributions were observed with average EC50 values of 0.7740 and 1.1561 μg mL−1, respectively. Eleven picoxystrobin-resistant mutants of C. truncatum and six mutants of C. gloeosporioides were acquired, with EC50 values varying from 5.40–152.96 and 13.53–28.30 μg mL−1, respectively. Compared to the parental isolates, mutants showed similar or higher relative fitness in conidial production and germination, and pathogenicity. Collectively, the resistance risk of C. truncatum and C. gloeosporioides to picoxystrobin is moderate to high. There was positive cross-resistance between picoxystrobin and pyraclostrobin, but not between picoxystrobin and fluazinam, difenoconazole, or propiconazole. The G143S mutation in Cyt b protein was detected in seven high-resistant mutants of C. truncatum (RF>100), and G137R occurred in four moderate-resistant mutants (RF<50). Contrastingly, there were no point mutations in Cyt b of any C. gloeosporioides mutants. Molecular docking confirmed that two mutations conferred different resistance levels to picoxystrobin. Under greenhouse trials, picoxystrobin did not control mutants with the G143S mutation, those bearing G137R or no point mutation were somewhat controlled, but at a lower level compared to wild-type isolates. These results showed that integrated management strategies should be implemented to preserve fungicide effectiveness.